Layanan Bimbingan Belajar Dengan Software Mindmaple_Lite_V165 Terhadap Kemampuan Elaborasi Siswa - Dharmayana, I Wayan; Nainggolan, Ester (JURNAL KONSELING GUSJIGANG, 2018)
This study aimed to described the effects of learning guidance services with mind maps software MindMaple_Lite_v165 on the ability to elaborate by students of SMP Negeri 6 Kota Bengkulu. The sample of this study was 21 students of class VIII F taken by using purposive sampling technique. This study was a Quasi Experiment with one group pre test and post test design. The instrument used in this study was ability test of elaborating Civics Education. Data were analyzed by using paired-samples t test. The results showed that there was significant difference between the scores of the ability to elaborate before treatment and those of the ability to elaborate after getting treatment with a value of t = - 14,361 (p < 0,05). It means that there was a significant effect of learning guidance services with software mind map to increase the ability of elaboration.